Kinetic Studies of the Glycerolysis of Urea to Glycerol Carbonate in the Presence of Amberlyst-15 as Catalyst - Hary Sulistyo; Wahyudi Budi Sediawan; Reviana Inda Dwi Suyatno; Indah Hartati (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Amberlyst-15, a strong acidic ion-exchange resin, has showed as a potential and an effective catalyst for the glycerolysis process of urea to glycerol carbonate. In this work, the kinetic model of the urea glycerolysis over Amberlyst-15 catalyst was investigated. The kinetic model was developed by considering simultaneous steps of urea dissolution in glycerol, mass transfer of urea and glycerol from the bulk of the liquid into the outer part of the catalyst, diffusion of urea and glycerol into the inner part of the particle through the catalyst pores, and irreversible second order reaction of urea and glycerol on the active sites. The irreversibility of second order reaction of urea glycerolysis was validated and proven. The proposed kinetic model was simulated and validated with the experimental data. The kinetic studies show that mechanism proposed works well. Furthermore, the activation energy was found to be 145.58 kJ.mol−1 and the collision factor was in 8.00×1010 (m3)2.kg−1.mol−1.s−1. The simulation result shows that the predicted liquid temperatures were close to the experimental temperature data. It also gave glycerol concentration profile inside the catalyst particle as a function of glycerolysis time and position. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).